Comparative analysis of five inspection techniques for the application in the diagnosis and treatment of osteoarticular tuberculosis. (November 2021) - Liu, Qibin; Chen, Xianxiang; Dai, Xiyong; Liu, Xiaoyu; Xu, Feng; Peng, Peng
Highlights: The Gene Xpert MTB/RIF test can quickly and accurately diagnose osteoarticular tuberculosis. Xpert MTB/RIF was found to have a higher sensitivity, specificity, and accuracy when compared to the other investigated methods for tuberculosis detection. Xpert MTB/RIF can quickly detect rifampicin resistance. Abstract: Objective: To evaluate five examination techniques in the diagnosis and treatment of osteoarticular tuberculosis (TB). Methods: Microbiological samples were collected from a total of 284 patients during the period August 2017 to December 2019 in Wuhan Pulmonary Hospital. The specimens were examined by acid-fast bacillus (AFB) smear microscopy, mycobacterial culture, PCR, T-SPOT. TB, and X-pert MTB/RIF rapid molecular detection. Results: The diagnostic sensitivity of the Xpert technology was 96.8% (116/120), specificity was 96.8% (58/60), the Youden index was 0.936, and the area under the receiver operating characteristic (ROC) curve was 0.967. The sensitivity and specificity of PCR were 84.2% (104/128) and 95.2% (76/80), respectively; the area under the ROC curve was 0.881. T-SPOT. TB had a detection sensitivity of 75.0% (12/16) and specificity of 85.0% (17/20). AFB smear microscopy had a sensitivity of 60.0% (75/125) and specificity of 95.8% (152/159). TB culture sensitivity was 58.1% (72/124) and specificity was 96.2% (73/76). The sensitivity and specificity of Xpert MTB/RIF for detecting rifampicin resistance were 100% (2/2) and 97.3% (73/75), respectively. Conclusions: The Xpert MTB/RIF technique was found to have a good diagnostic value. With an additional diagnosis of Rifampicin resistance, it was also useful in tuberculosis therapy.